Hydraulic optimisation of service reservoirs to maintain water quality in distribution systems - O'Neill, S. (Cranfield University, 2001)
Water supply utilities worldwide are under pressure to meet stringent water quality and supply demands Service reservoirs (SRs) or treated water storage reservoirs have been built for the dual function of maintaining pressure and providing a buffer of supply. A balance must be sought between operational objectives in order to ensure adequate supply in the event of unforeseen incidents whilst limiting the maximum time between abstraction and the point of use. Existing reservoirs can have storage times between a couple of hours and several tens of days. The resulting degradation in water quality ensures that it is no longer feasible to focus on point of abstraction treatment as a means of assuring that all customer and legislator expectations are continuously met. This thesis aims to evaluate the hydraulic design and operation of service reservoirs in the UK and evaluate methods to improve performance. A generic study of mixing in service reservoirs has been conducted using physical modelling techniques. The segregation of generic groups of reservoirs for modelling was defined after a comprehensive survey of 166 operational full-scale reservoirs was completed. Reservoir groups are defined in terms of shape and aspect ratio. Steady state, transient tests and intermittent flow — "fill and draw" tracer tests were conducted. Step and pulse trace injection techniques were used. Dye tests were conducted for flow visualisation and the results recorded with photographic stills and a digital video recorder. Water age is quantified in terms of cumulative percentage of injected trace recovery. Flow fractions in terms of dead space, plug flow and mixed flow are quantified for each series of tests using a multiparameter model. Alternative methods of quantification. dead areas are evaluated and discussed. Key reservoir performance indicators are defined and linked to water quality issues. The results presented have been compiled into a design guide document to enable water utility managers to simply evaluate existing reservoir designs and evaluate potential operational and retrofit options for optimisation. Case studies of full-scale reservoirs applications are presented.